1996
DOI: 10.1172/jci118754
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular lactate- and pyruvate-interconversion rates are increased in muscle tissue of non-insulin-dependent diabetic individuals.

Abstract: The contribution of muscle tissues of non-insulin-dependent diabetes mellitus (NIDDM) patients to blood lactate appearance remains undefined. To gain insight on intracellular pyruvate/lactate metabolism, the postabsorptive forearm metabolism of glucose, lactate, FFA, and ketone bodies (KB) was assessed in seven obese non-insulin-dependent diabetic patients (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 45 publications
6
51
0
Order By: Relevance
“…In corroboration with previous studies in healthy subjects, we found that both skeletal muscle and adipose tissue are significant sources of lactate production in the postabsorptive state and that insulin stimulates net lactate release in both tissues (1,5,11,14,16,17,19,(21)(22)(23). The basal lactate release was, as expected, higher in skeletal muscle than in adipose tissue.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In corroboration with previous studies in healthy subjects, we found that both skeletal muscle and adipose tissue are significant sources of lactate production in the postabsorptive state and that insulin stimulates net lactate release in both tissues (1,5,11,14,16,17,19,(21)(22)(23). The basal lactate release was, as expected, higher in skeletal muscle than in adipose tissue.…”
Section: Discussionsupporting
confidence: 92%
“…In skeletal muscle, studies using arteriovenous balance and isotope techniques have registered both increased and similar rates of skeletal muscle lactate release in type 2 diabetics compared with controls (1,5,9). In adipose tissue, comparison of lactate release with microdialysis in lean and obese men has shown impaired ability to increase lactate production following oral glucose in obese subjects (21).…”
mentioning
confidence: 99%
“…These observations suggest that the basal level of insulinemia is important in modulating the intracellular fate of the glucose taken up by peripheral tissues and that a dysfunction in basal insulin secretion may contribute to the accelerated release of FFAs and lactate (31). The latter is a preferential gluconeogenic substrate, and the former provides the energy required for driving gluconeogenesis; the final result is enhanced EGP and fasting hyperglycemia.…”
Section: Basal Insulin Secretionmentioning
confidence: 96%
“…The intracellularly produced lactate leaves the cell via simple diffusion and two proteins: monocarboxylate transporter (MCT) 1 and MCT4 [53]. The density of MCT1 and/or MCT4 in human skeletal muscle is elevated after endurance training [54][55][56] and resting blood lactate concentrations may be elevated in patients with type 2 diabetes [57][58][59]. One randomized controlled trial [22] reported a significant increase of MCT after resistance exercise.…”
Section: Othersmentioning
confidence: 99%